First fossil Lamprosomatinae leaf beetles (Coleoptera: Chrysomelidae) with descriptions of new genera and species from Baltic amber - Bukejs, Andris; Nadein, Konstantin (Zootaxa, 2015)
In the current paper the first fossil representatives of leaf-beetles from the subfamily Lamprosomatinae (Coleoptera: Chrysomelidae) are described and illustrated from Upper Eocene Baltic amber: Succinoomorphus warchalowskii gen. et sp. nov., Archelamprosomius balticus gen. et sp. nov., and Archelamprosomius kirejtshuki sp. nov. A key to fossil Lamprosomatinae is provided.